Protection against allergic airway inflammation during the chronic and acute phases of Trichinella spiralis infection. Issue 1 (24th December 2012) - Aranzamendi, C.; de, A.; Kuiper, R.; Boog, C. J. P.; van, W.; Rutten, V.; Pinelli, E.
Summary Background Modulation of the host immune response by helminths has been reported to be essential for parasite survival and also to benefit the host by suppressing inflammatory diseases such as allergies. We have previously shown that excretory‐secretory products of Trichinella spiralis muscle larvae have immunomodulatory properties and induce in vitro the expansion of CD4+CD25+FOXP3+ Treg cells in a TGF‐β‐dependent manner. Objective We aimed at determining the effect of the acute (intestinal) and the chronic (muscle) phase of T. spiralis infection on experimental allergic airway inflammation (EAAI) to Ovalbumin (OVA) and the involvement of Treg cells. Methods The chronic phase was established before OVA‐sensitization/challenge and the acute phase at two‐time points, before and after OVA‐sensitization. Mice were infected with 400 T. spiralis larvae and after euthanasia different pathological features of EAAI were measured. Adoptive transfer of CD4+ T cells from Trichinella infected mice to OVA sensitized/challenged recipients was also performed. Results We found that the chronic as well as the acute phase of Trichinella infection suppress EAAI as indicated by reduction in airway inflammation, OVA‐specific IgE levels in sera, Th2‐cytokine production and eosinophils in bronchoalveolar lavage. This protective effect was found to be stronger during the chronic phase and to be associated with increased numbers of splenic CD4+CD25+FOXP3+ Treg cells with suppressive activity. Adoptive transfer of splenic CD4+ T cells from chronically infected mice with elevated numbers of Treg cells resulted in partial protection against EAAI. Conclusions and Clinical Relevance These results demonstrate that the protective effect of T. spiralis on EAAI increases as infection progresses from the acute to the chronic phase. Here, Treg cells may play an essential role in the suppression of EAAI. Elucidating the mechanisms and molecular helminth structures responsible for this regulatory process is relevant to develop alternative tools for preventing or treating allergic asthma.